Adherence to the use of the surgical checklist for patient safety - Eliane Cristina Sanches Maziero; Ana Elisa Bauer de Camargo Silva; Maria de Fátima Mantovani; Elaine Drehmer de Almeida Cruz
Objective: Evaluate adherence to the checklist of the Programa Cirurgias Seguras (safe surgery programme) at a teaching hospital. Methods: Evaluative study conducted at a teaching hospital in the south of Brazil in 2012. Data were collected by means of non-participant observation in 20 hip and knee replacement surgeries and an instrument that was created for research based on the checklist and used by the institution. Results: In the observed procedures (n = 20) there was significant adhesion (p<0.05) to the instrument in relation to the verification of documentation, fasting, hair removal in the surgical site, absence of nail varnish and accessories, identification of the patient and surgical site on admission to the surgical unit, availability of blood and functionality of materials. However, there was no significant adherence to the checklist in the operating room in relation to patient identification, procedure and laterality, team introduction, surgical break and materials count. Conclusion: The results showed that the items on the checklist were verified nonverbally and there was no significant adherence to the instrument.